2016
DOI: 10.1093/mnras/stw2934
|View full text |Cite
|
Sign up to set email alerts
|

Bar-driven evolution and quenching of spiral galaxies in cosmological simulations

Abstract: We analyse the output of the hi-res cosmological "zoom-in" hydrodynamical simulation ErisBH to study self-consistently the formation of a strong stellar bar in a Milky Way-type galaxy and its effect on the galactic structure as well as on the central gas distribution and star formation. The simulation includes radiative cooling, star formation, SN feedback and a central massive black hole wich is undergoing gas accretion and is heating the surroundings via thermal AGN feedback. A large central region in the Er… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
109
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(121 citation statements)
references
References 96 publications
11
109
0
Order By: Relevance
“…In the core region, barred galaxies have lower sSFR than nonbarred galaxies. It has been suggested that a bar structure can quench star formation of galaxies (Cheung et al 2013;Gavazzi et al 2015;Zhou et al 2015;Spinoso et al 2017). Numerical simulation of a bar formation in a galaxy shows that gas is rapidly transferred toward the central region on the onset of the bar structure, and that the gas transfer triggers a burst of star formation in the central region of the galaxy.…”
Section: Radial Variation Of the Spatially-resolved Sfmsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the core region, barred galaxies have lower sSFR than nonbarred galaxies. It has been suggested that a bar structure can quench star formation of galaxies (Cheung et al 2013;Gavazzi et al 2015;Zhou et al 2015;Spinoso et al 2017). Numerical simulation of a bar formation in a galaxy shows that gas is rapidly transferred toward the central region on the onset of the bar structure, and that the gas transfer triggers a burst of star formation in the central region of the galaxy.…”
Section: Radial Variation Of the Spatially-resolved Sfmsmentioning
confidence: 99%
“…Numerical simulation of a bar formation in a galaxy shows that gas is rapidly transferred toward the central region on the onset of the bar structure, and that the gas transfer triggers a burst of star formation in the central region of the galaxy. As the gas being transferred to the central region, gas within the bar's corotation radius is consumed and SFR within the radius can be suppressed finally (Spinoso et al 2017).…”
Section: Radial Variation Of the Spatially-resolved Sfmsmentioning
confidence: 99%
“…An analysis of the ErisBH simulation demonstrated that the formation of a bar in a galaxy with a quiet merger history can quench its star formation on kiloparsec scales (Spinoso et al 2017). They showed that gas can be removed rapidly by the bar in the inner region, preventing any further strong star formation.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Scannapieco & Athanassoula (2012) studied the properties of two bars of Milky Way-mass galaxies at z = 0, a subsample of the simulations described in Scannapieco et al (2009). Subsequent work developed by Goz et al (2015), Okamoto et al (2015), and Spinoso et al (2017), focused on the evolution of bar properties for one or two galaxies. Although the aforementioned works were generally in good agreement with both previous idealised simulations and observations, they lacked of a statistically representative sample to verify if these cosmological simulations could reproduce the statistical properties of barred galaxies.…”
mentioning
confidence: 99%